Rząd Roberta Mugabe wobec polityki Stanów Zjednoczonych Ameryki na południu Afryki (1980–1987) - Szczepańska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2015)
The purpose of the article is presentation of the Republic of Zimbabwe attitude towards American policy in Southern Africa and some elements of relations between countries. An initial relations between Zimbabwe and US was very correct but after first two years (after Zimbabwe’s independence in 1980) it became colder. The US hoped to include Zimbabwe in their sphere of influence. Washington wanted wider influences in Southern Africa thus they engaged diplomatic in civil war in Angola and did not agree with independence of Namibia. They kept relations with RSA also. Zimbabwe, as a regional leader, did not agree with the American policy. American activities in Southern Africa were a reason of extended conflicts in Angola and Namibia. Different opinions the Zimbabwe and US governments were an end of relations between countries. The Harare policy was not a direct reason of solution conflicts in Southern Africa but the Robert Mugabe actions strengthen the position of Zimbabwe in Africa and in the world.